1997
DOI: 10.1063/1.118497
|View full text |Cite
|
Sign up to set email alerts
|

Effects of interface charges on imprint of epitaxial Bi4Ti3O12 thin films

Abstract: Growth, structure, and properties of all-epitaxial ferroelectric ( Bi , La ) 4 Ti 3 O 12 ∕ Pb ( Zr 0.4 Ti 0.6 ) O 3 ∕ ( Bi , La ) 4 Ti 3 O 12 trilayered thin films on Sr Ru O 3 -covered Sr Ti O 3 ( 011 ) substrates Appl. Phys. Lett. 86, 082906 (2005); 10.1063/1.1864248 ( Bi , La ) 4 Ti 3 O 12 (BLT) thin films grown from nanocrystalline perovskite nuclei for ferroelectric memory devices Appl. Phys. Lett. 85, 4118 (2004); 10.1063/1.1812840 Effect of oxygen stoichiometry on the ferroelectric property of epitaxial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
28
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 9 publications
4
28
0
Order By: Relevance
“…Several authors have also suggested the space charge developed by the trapping of carriers in these oxygen vacancies is responsible for the imprint effect. 18,25,26 . The presence of an oxygen vacancy, therefore, impedes the displacement of Ti 4ϩ .…”
Section: B Asymmetric Distribution Of Oxygen Vacanciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have also suggested the space charge developed by the trapping of carriers in these oxygen vacancies is responsible for the imprint effect. 18,25,26 . The presence of an oxygen vacancy, therefore, impedes the displacement of Ti 4ϩ .…”
Section: B Asymmetric Distribution Of Oxygen Vacanciesmentioning
confidence: 99%
“…18,26,32,33 The oxygen vacancy itself bears a positive charge by releasing electrons. Experimental results also reveal that holes are injected across the electrode film interface, 34 and that oxygen vacancies or their related defect complexes are hole traps.…”
Section: Effect Of Space Chargementioning
confidence: 99%
“…Since the PZT capacitors with noble metal electrodes like Pt exhibit a significant polarization loss when subject to bipolar switching pulses, in the past decade, for the growth of fatigue-free PZT capacitors and especially in the epitaxial form, various oxide electrodes such as La 0.5 Sr 0.5 CoO 3 (LSCO), SrRuO 3 (SRO), La 0.7 Sr 0.3 MnO 3 (LSMO), and LaNiO 3 (LNO) have been employed. [3][4][5][6][7][8]11,12 For epitaxial LSCO/PZT/LSCO capacitors, however, when exposed to reducing atmosphere for device fabrication, a large voltage offset was observed. [3][4][5] This process-induced imprint behavior was greatly complicated by the instability of the LSCO layer at reduced oxygen pressures, 5,13 and rarely examined for the other oxide electrodes.…”
mentioning
confidence: 99%
“…However, there is a lack of understanding on the formation of the internal field. Different models, such as the aligned dipolar defect complexes and asymmetric distribution of charged defects through a bulk thin film, 2-5 and a built-in electric field or a nonswitching layer at the ferroelectric-electrode interface, [6][7][8][9] have been proposed to explain the asymmetric behavior of ferroelectric capacitors.…”
mentioning
confidence: 99%
See 1 more Smart Citation